Penggunaan Teknologi Informasi (IBS Collect) Terhadap Kepuasan Nasabah Pada Lembaga Perkreditan Desa (LPD) Desa Adat Celuk - Putu Pande Yudiastra; Ni Luh Ged Putu Purnawa; Gusti Ngurah Mega Nata (Jurnal Ilmiah Satyagraha, 2024)
ABSTRACT The aim of this research is to find outThe influence of IBS (Integrated Micro Banking System) technology services on customer satisfaction at LPD Celuk Sukawati, Gianyar. The research method in this study used a questionnaire distributed to 100 customers from LPD Celuk Sukawati, Gianyar. The analysis technique used is simple linear regression analysis. Based on the results of the analysis, it was found that the influence of IBS (Integrated Micro Banking System) technology services on customer satisfaction at LPD Celuk Sukawati, Gianyar was positive and significant for customer satisfaction at LPD Celuk Sukawati Gianyar. This is based on a regression coefficient of 0.838 with a determination of 74.4%, which means that the influence of IBS (Integrated Micro Banking System) technology services has an effect of 74.4% on customer satisfaction at LPD Celuk Sukawati, Gianyar, while the remaining 26.6% was influenced by other variables which were not examined in this study. Apart from that, with the t test, the calculated t-value is obtained16.893 with a significance value of 0.000, because the significance value of 0.000 is smaller than 0.05, meaning there is a positive and significant influenceIBS (Integrated Micro Banking System) technology services on customer satisfaction at LPD Celuk Sukawati, Gianyar.